2014
DOI: 10.1016/j.jpag.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Cryopreservation for Fertility Preservation in Postpubertal Female Children at Risk for Premature Ovarian Failure Due to Accelerated Follicle Loss in Turner Syndrome or Cancer Treatments

Abstract: Objective To preliminarily study the feasibility of oocyte cryopreservation in post-pubertal girls aged between 13 and 15 years who were at risk for premature ovarian failure due to the accelerated follicle loss associated with Turner’s Syndrome or cancer treatments. Design Retrospective cohort and review of literature. Setting Academic fertility preservation unit. Participants Three girls diagnosed with Turner syndrome, one girl diagnosed with germ-cell tumor and one girl diagnosed with lymphoblastic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 26 publications
3
66
1
2
Order By: Relevance
“…Attempts have been made by the freezing of ovarian cortical tissue for young adolescent girls or by the collection of stimulated mature oocytes as part of an IVF cycle for older girls; however, due to the restricted oocyte number, these techniques are not routine and have had to date limited success (150) but may offer promise in the future (242). Furthermore, when a woman with Turner syndrome commences fertility treatment in view of the associated increased risk of cardiovascular-related mortality in pregnancy, they should be cared for under specialized care, and indeed, Turner syndrome should be considered a relative contraindication to pregnancy (266).…”
Section: Geneticmentioning
confidence: 99%
“…Attempts have been made by the freezing of ovarian cortical tissue for young adolescent girls or by the collection of stimulated mature oocytes as part of an IVF cycle for older girls; however, due to the restricted oocyte number, these techniques are not routine and have had to date limited success (150) but may offer promise in the future (242). Furthermore, when a woman with Turner syndrome commences fertility treatment in view of the associated increased risk of cardiovascular-related mortality in pregnancy, they should be cared for under specialized care, and indeed, Turner syndrome should be considered a relative contraindication to pregnancy (266).…”
Section: Geneticmentioning
confidence: 99%
“…В последние годы в медицинской литературе большое внимание уделяется медико-социаль-ным факторам формирования репродуктивно-го здоровья у девушек-подростков как будущих матерей [16,17,18,19,20].…”
Section: Discussionunclassified
“…Oktay et al have reported on successful oocyte cryopreservation in post-pubertal children with mosaic TS 25,26 . In these reports, three girls aged 13–15 with mosaic TS were identified to have decreased ovarian reserve by serum AMH hormone measurements and antral follicle counts on ultrasound examinations.…”
Section: Fertility Preservation Strategiesmentioning
confidence: 99%
“…Because the ovarian reserve can be lost even during the very first few years of life in full TS cases, ovarian tissue cryopreservation may be the only, albeit experimental, option for this population. While ovarian reserve evaluation may be difficult in children under the age of 5 20 , a combination of serum FSH, Inhibin-B, AMH and antral follicle counts on ultrasound may provide useful information 23,25 .…”
Section: Fertility Preservation Strategiesmentioning
confidence: 99%